Alterations in antioxidant enzyme status with lipid peroxidation in β thalassemia major patients (International Journal of Pharmacy and Life Sciences, 2012)
β thalassemia major is an inherited disease resulting from reduction or total lack of beta globin chains. Patients with this disease need repeated blood transfusion for survival, this may cause oxidative stress. Although some reports suggest endogenous free radical damage in thalassemia, there remains discrepancy in the status of antioxidant enzymes. The prevalence of β thalassemia major is high in tribal and non tribal population in area around Dhule, Nandurbar and Jalgaon districts in Maharashtra. So the present study was initiated to evaluate the status of antioxidant enzymes with lipid peroxidation in β thalassemia major patients. Blood samples were collected from 100 subjects (50 β-thalassemia major patients and 50 healthy controls). Serum levels of iron, total iron binding capacity (TIBC), ferritin, MDA and TAS activity were determined using conventional methods. Serum Iron, MDA were significantly increased while TIBC, SOD and GPX activities were significantly decreased in β-thalassemia major patients as compared to healthy individuals. Our results suggest that iron overload causes peroxidative damage in beta-thalassemia and antioxidant systems try to compensate for reducing lipid peroxidation to lower tissue damage.